Political Economic Analysis And Consection Of Development: Mxgp Study Of Mataram City - Dermawan, Ariy; Agustina, Nurillah; Nuraini, Nuraini; Soniati, Soniati; Harunnisa, Ipa; Jannah, Jumratul; Afsarin, Afsarin; Gani, Arif Rahman (CV. ITTC INDONESIA, 2025)
The 2024 MXGP, to be held at the Selaparang Circuit in Mataram City, provides a comprehensive overview of the political and economic impacts of development and tourism. Due to its better infrastructure, Selaparang was chosen as the new location, instead of the Samota Circuit, which required close coordination between the local government and the event organizers. Although there were administrative challenges to overcome, such as tax arrears, these were resolved through fruitful dialogue, highlighting the importance of teamwork in overcoming challenges. The event will increase hotel occupancy, attract more tourists, and provide a major economic boost to the area. Local businesses will benefit from higher tourism-related revenues as well as increased participation from micro, small, and medium enterprises. Visitors will also drive economic diversity and job development, which will help industries such as transportation, hospitality, and retail. By promoting environmentally friendly projects and environmentally conscious tourism, the 2024 MXGP is well positioned to act as a catalyst for sustainable infrastructure development. In addition, the local government’s reputation has demonstrated its ability to host major international meetings. Lombok will ultimately reap long-term social and economic benefits from MXGP 2024, which will strengthen the island as a leading international sports tourism destination.